Impact of Genetic Variants on Pregabalin Pharmacokinetics and Safety - Sofía Calleja; Andrea Rodríguez-López; Dolores Ochoa; Sergio Luquero; Marcos Navares-Gómez; Manuel Román; Gina Mejia-Abril; Samuel Martín-Vilchez; Francisco Abad-Santos; Pablo Zubiaur (Pharmaceuticals)
Background/Objectives: Pregabalin is a useful therapeutic option for patients with anxiety or neuropathic pain. Genetic variants in certain genes encoding for transporters related to absorption and distribution could have an impact on the efficacy and safety of the drug. Furthermore, extreme phenotypes in metabolic enzymes could alter pregabalin-limited metabolism. Methods: In this study, we included 24 healthy volunteers participating in a bioequivalence clinical trial and administered pregabalin 300 mg orally; 23 subjects were genotyped for 114 variants in 31 candidate genes, and we explored their impact on pregabalin pharmacokinetics and safety. Results: The uncorrected mean (±SD) of AUC∞ and Cmax were 61,097 ± 14,762 ng*h/mL and 7802 ± 1659 ng/mL, respectively, which were significantly higher in females than in males (p = 0.002 and p = 0.001, respectively), with no differences in dose/weight (DW)- corrected exposure metrics. NAT2 slow acetylators (SAs) showed a 16–18% increase in exposure compared to intermediate (IAs) and normal (NAs) acetylators; NAT2 SAs exhibited a 25% higher t1/2 as compared with NAT2 IAs and 58% higher compared to NAT2 NAs. In contrast, neither the NAT2 phenotype nor other genetic variants were related to pregabalin adverse drug reaction (ADR) occurrence. On the contrary, sex and sex-related exposure differences (i.e., females and their higher exposure compared to males) were the main predictors of ADR occurrence. Conclusions: Our findings suggest that NAT2 could be partially responsible for the minor proportion of pregabalin metabolism, but the effect of NAT2 phenotype does not seem clinically relevant. Therefore, pharmacogenetic biomarkers appear to play a restrained role in pregabalin pharmacotherapy.